Information widths - Korneichuk, N. P. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We introduce the notions of adaptive information widths of a set in a metric space and consider the problem of comparing them with nonadaptive widths. Exact results are obtained for one class of continuous functions that is not centrally symmetric.